1987
DOI: 10.1111/j.1469-7610.1987.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Voices in Unison: Stressful Events in the Lives of Children in Six Countries

Abstract: A 20-event, 7-point scale on the stressfulness of selected unpleasant experiences was administered to 1814 children in Australia, Canada, Egypt, Japan, the Philippines, and the U.S.A. (two groups). Responses indicated that, among these 3rd through 9th graders, there is a remarkable degree of agreement not only in the stress ratings but also in the reported incidences of life events. Granted certain cultural contrasts, the overall findings gave credence to the presence of widespread, common perceptions and atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 11 publications
9
23
0
Order By: Relevance
“…Generally, researchers have obtained findings similar to those of the 6-country study of Yamamoto et al (1987) who compared 1814 children in Australia, Canada, Egypt, Japan, Philippines and USA and concluded that: "Amongst these 3rd through 8th graders, there is remarkable agreement not only in stress ratings but also in the reported incidence of life events." (p 855) Parallel to this work several researchers have compared measures of adjustment, such as self-concept and self-esteem in adolescents in different cultural settings (e.g.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Generally, researchers have obtained findings similar to those of the 6-country study of Yamamoto et al (1987) who compared 1814 children in Australia, Canada, Egypt, Japan, Philippines and USA and concluded that: "Amongst these 3rd through 8th graders, there is remarkable agreement not only in stress ratings but also in the reported incidence of life events." (p 855) Parallel to this work several researchers have compared measures of adjustment, such as self-concept and self-esteem in adolescents in different cultural settings (e.g.…”
Section: Introductionsupporting
confidence: 62%
“…A number of writers have compared levels of stress in adolescents across different national boundaries including Canada, United States, Britain, Malaysia, India, Hong Kong and The Philippines (Driver, 1972;Agrawal, 1978;Yamamoto, Soliman, Parsons and Davies, 1987;Bochner, 1994;Dharwan et al, 1995;Bagley and Mallick, 1995;Watkins and Gerong, 1997;Gibson-Cline, 1996). Generally, researchers have obtained findings similar to those of the 6-country study of Yamamoto et al (1987) who compared 1814 children in Australia, Canada, Egypt, Japan, Philippines and USA and concluded that: "Amongst these 3rd through 8th graders, there is remarkable agreement not only in stress ratings but also in the reported incidence of life events."…”
Section: Introductionmentioning
confidence: 99%
“…2 At the opposite end was the event of the arrival of a new sibling with the sole exception, as already noted, of the children in Poland whose ratings made the typically rather stressful experience of "getting lost in some strange place" the least upsetting of all. Other events that were rated towards the lower end of stressfulness included "Getting up in front of the class to give a report," "Losing in any game or sports," "Going to a dentist," and "Being picked last on a team."…”
Section: Scale Valuementioning
confidence: 93%
“…Among the children, our previous inquiries have suggested surprisingly similar patterns of assessments of the stressfulness of potentially upsetting experiences within the family, school, and other familiar social settings. 2 We have also found that these views of children do not parallel closely those of adults making inferences on the possible impact of the stress on the child. 3 While, for instance, three subgroups of American professionals were practically unanimous in their estimation of children's judgments (all correlations being .97), the assessments by the adults correlated only .68 with the ratings by the U.S. children themselves.…”
mentioning
confidence: 88%
“…Yamamoto and colleagues (Yamamoto and Byrnes, 1984;Yamamoto, Soliman, Parsons, and Davies, 1987) have compared the incidence and perception of stressful life events across cultures and found a high degree of agreement among 3rd-9th graders in both stress ratings and the incidence of life events, prompting them to hypothesize a common "culture of childhood." The most significant life stressors rated by these children were losing a parent, going blind, being academically retained, wetting in class, and witnessing fights between parents.…”
Section: Measuring Stressorsmentioning
confidence: 95%